2012
DOI: 10.1128/cvi.05556-11
|View full text |Cite
|
Sign up to set email alerts
|

Phase 1 Study of a Recombinant Mutant Protective Antigen of Bacillus anthracis

Abstract: A phase 1 study of a recombinant mutant protective antigen (rPA) vaccine was conducted in 186 healthy adults aged 18 to 45 years. Volunteers were randomized to receive one of three formulations of rPA (formalin treated, alum adsorbed, or both), in 10-or 20-g dosages each, or the licensed vaccine, AVA. Three injections were given at 2-month intervals and a 4th 1 year after the 3rd. Vaccinees were examined at the clinic once following each injection, at 48 to 72 h postinjection. Adverse reactions were recorded i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 31 publications
1
15
0
1
Order By: Relevance
“…However, work from our group has previously shown that the toxin-neutralizing quality of PA antibodies from AVA recipients is highly variable (42). This has led to research seeking to develop more effective anthrax vaccines, including recombinant PA (43)(44)(45)(46), alternative adjuvants (47,48), and additional vaccine targets (49)(50)(51).…”
Section: Discussionmentioning
confidence: 99%
“…However, work from our group has previously shown that the toxin-neutralizing quality of PA antibodies from AVA recipients is highly variable (42). This has led to research seeking to develop more effective anthrax vaccines, including recombinant PA (43)(44)(45)(46), alternative adjuvants (47,48), and additional vaccine targets (49)(50)(51).…”
Section: Discussionmentioning
confidence: 99%
“…Recently advances in enhancement of the immune response through cofactors targeting TLR signaling have been reported as well (219). A new vaccine using recombinant PA has not yet been approved; however, several, including those utilizing mutant PA variants with less toxicity and higher immunogenicity, are in development or clinical trials (17,25,68,86,118,136,188,189,277).…”
Section: Vaccinesmentioning
confidence: 99%
“…Currently, most anthrax vaccines are toxin‐based. The FDA‐licensed anthrax vaccine BioThrax ® , also known as AVA (Anthrax Vaccine Adsorbed, Emergent Biosolutions, Rockville, MD), contains a PA‐aluminum hydroxide‐adsorbed precipitate derived from a B. anthracis pXO1 + pXO2 − culture supernatant, and rPA‐based next‐generation anthrax vaccines are currently undergoing clinical trials (Brown et al ., ; Bellanti et al ., ). In addition, vaccine‐engineered plasmids expressing PA and LF can protect A/J mice against lethal challenge with aerosolized B. anthracis spores (Albrecht et al ., , b).…”
Section: Tna Serum Fractions Compared With Total Antigen‐specific Iggmentioning
confidence: 99%